Synthesis of a 4-aryl-2-anilinopyrimidine using a germanium-functionalised non-cross-linked polystyrene (NCPS) support - Srikaran, R.; Kontorgiorgis, C.A.; Warren, S.A.; Pisaneschi, F.; Spivey, A.C. (My University, 2013)
The use of a germanium-functionalised non-cross-linked polystyrene (NCPS) support to aid the preparation of a 2-anilino-4-arylpyrimidine is described. This compound is a key intermediate en route to various IKK-2 and JNK inhibitors.
Keywords: germanium; IKK; JNK; kinase; liquid-phase organic synthesis (LPOS); non-cross-linked polystyrene (NCPS); polymerization; pyrimidine; soluble polymer